Protocolo de agricultura de precisão como ferramenta de sustentabilidade - Fadanelli , Samuel Citon (2021)
New configurations in grain production in small rural properties provide great challenges for family farmers in the western region of Paraná. In this context, actors who seek to develop new techniques that can provide greater sustainability to the use of natural resources with the objective of improving the physicochemical characteristics of soils are included. In this context is precision agriculture, a technological package developed for large properties however, through the experiences of technicians from the Emater Institute of Tupãssi, Paraná, it was possible to develop a precision agriculture protocol for small properties through the methodology of grids by cells. Therefore, it was possible to build a flow diagram of the activities carried out by the program, from the beginning of its creation to the operational processes, which presented an estimated return on investment of 26.30% for the municipality with productivity increase data for 3 properties monitored during 3 soy and corn harvests, therefore the PA project presents a positive perspective of promoting sustainability and rational use of natural resources.